PILIHAN KARIR MENGAJAR MAHASISWA PENDIDIKAN EKONOMI (Kajian Motivasi Karir Mengajar, Career Self Efficacy, Status Sosial Ekonomi, Minat menjadi Guru Terhadap Prestasi Akademik) - Setiaji, Khasan (Fakultas Ekonomi, Universitas Negeri Semarang, 2015)
The research aims to test the influence teaching career motivation, career self-efficacy and social economic status of academic achievement through its interest in becoming a teacher. The populations of this study were all students of Economic Education of first semester the academic year 2012/2013 which still in the career choice process and content. Proportional random samples technique was used in this study. The collecting data used the question form and documentation, while for analyzing the data using path analysis.Research findings show that teaching career motivation, career self-efficacy and social economic status has a positive and significant influence to the academic achievement through its interest in becoming a teacher. Based on this research finding, it can be suggested that (1) an attempt to cultivate interest of being a teacher and academic achievement can be conducted by increasing career motivation, career self-efficacy, and parents support, (2) the process of admission or the preparation of teachers need to pay attention to such as talent, psychological aspects interest, motivation, and career self-efficacy to get the input quality, (3) provide learning facilities for poor family student who are facing trouble for higher study.